Nuclear terrorism - Rutić, Srđan Z. (Vojnotehnički glasnik / Military Technical Courier, 2015)
In the paper, the review of the ways of manifestation of terrorism and nuclear weapons ionizing radiation as a special kind of terrorism. The analysis of opportunities coming into possession of nuclear weapons by terrorist groups and apply the same for terrorist purposes. Analyzed the forms and methods of terrorist activities nuclear means. It was concluded that nuclear terrorism includes various forms of threats, which may include not only nuclear weapons but also the sources of ionizing radiation for terrorist purposes. It was also concluded that the International Atomic Energy Agency (IAEA) with countries that have signed the Treaty on the Nonproliferation of Nuclear Weapons and other international treaties seek to terrorist organizations to be an insurmountable obstacle to the purchase of the necessary nuclear materials and equipment necessary for the construction of nuclear weapons.
Keywords: Weapons; Neclear terorism; Nuclear weapons; terrorism